Analysis of Business Profitability Kisar Sheep In Kisar Island, Maluku Barat Daya Regency - Welerubun, Inggrid (Program Studi Di Luar Kampus Utama Universitas Pattimura, 2020)
The study aimed to analyze the profitability of Kisar sheep farmers in Kisar. The role of the livestock in the structure of income is potentially important especially in the welfare of local farmers. This research was conducted in April to June 2014 in Kisar Island, Kabupaten Maluku Barat Daya. The location of the study was determined intentionally (purposive) because only Kisar has the population of Kisar sheep livestock. The respondents were determined by proportionate random sampling. The chosen location was three villages named Pura-Pura, Oirata and Wonreli. The Respondents were drawn as many as 100 people were chosen randomly. The collected data were analyzed descriptively. The result of the study showed that Kisar sheep farmers’ income was IDR. 202,169.9/year for a small scale, IDR. 2.509,475.2/year for a medium scale and IDR 5,891,408.9 /year for a large scale. Based on the analysis, the percentage of the profitability achieved was small scale was 20,5%, middle scale was 25,95%, and big scale was 58,25%. It is said to be profitable because the value of profitability is bigger than the bank credit interest rate of 5%.